IMPROVING THE MANAGEMENT AND COMPETENCE OF DYNAMO WORKSHOP TECHNICIANS THROUGH THE DESIGN OF A LINEAR ACTUATOR-BASED BEARING RELEASE PULLER - Yahya, Wachid; Ramelan , Utomo; Kurniawan, Dimas Dwi; Fadila , Maulina Isza (Abdi Masya, 2024)
This activity aims to improve workshop management and technician competence in the dynamo maintenance field by designing an innovative tool in the form of a linear actuator-based bearing removal puller. Dynamo workshops often face challenges in the bearing removal process, which is time-consuming, requires a lot of energy, and is prone to causing damage to dynamo components. Therefore, to overcome these problems, an automatic bearing removal tool using linear actuator technology was developed. This tool is expected to increase the work efficiency of technicians by speeding up the bearing removal process, reducing the risk of component damage, and increasing work safety. This activity has three stages: preparation, implementation, and evaluation in its development using an experimental approach and training skills, where tools designed based on the needs of industrial partners Kalimasada at Sukoharjo Regency were tested and continued with training on the use of tools and providing reinforcement on workshop management. The results show that using a linear actuator-based bearing release puller can reduce the release time faster to increase technician confidence in performing dynamo maintenance. Thus, this innovation significantly improves dynamo workshop operational management and technician competence.